PROSES PERENCANAAN PENGEMBANGAN BUDIDAYA PERIKANAN DI KOTA PEKALONGAN - Mochtar Sanusi; Mardiyono .; Suryadi . (REFORMASI, 2014)
Based on declining capture fisheries production in Pekalongan in recent years due to over-fishing in the Java Sea, then efforts to increase fish production is currently directed towards the development of aquaculture. Potential aquaculture about 18% of the area of Pekalongan, but it has not made a significant contribution to the income of the people. The process of aquaculture development planning as an early stage in the process of regional development is expected to absorb the aspirations of the people and be able to explore the potential of the area. This research aims to describe and analyze the process of aquaculture development planning in Pekalongan, supporting factors and obstacles in process of aquaculture development planning in Pekalongan. The method used is qualitative descriptive approach. Analysis of the data by using analysis Miles and Huberman. Based on the results of the study indicate that partisipation of stakeholder are less involved, planning dominated by top-down and technocratic approach, factors supporting are fisheries personnel, strategic plan documents, legislation, and aquaculture potential, while inhibiting factors, the lack of skilled human resources in the field of planning, less participation of fish farmers, coordination still weak, and limited budget.